Documents of the notary Victor Gaffaro. For a virtual archive of Venetian documents drawn up in Constantinople (1336-1341) - Andrea Nanetti (2016)
The paper is a result of a research carried out in the State Archives of Venice in 1999. It presents the documentary evidence and the historical study of the Venetian notary Victor Gaffaro, who was the chancellor of the Venetian ‘bailus’ in Constantinople from 1336 to 1341.